2017
DOI: 10.1002/2017jc012830
|View full text |Cite
|
Sign up to set email alerts
|

Episodic surface intrusions in the Yellow Sea during relaxation of northerly winds

Abstract: The surface currents over the Yellow and East China Seas are mapped from the Geostationary Ocean Color Imager (GOCI). Based on a composite of six intrusion events in January–April, the strong northward surface current in the Yellow Sea is shown to be concentrated along the deep trough, accompanied by a broad northward surface current over the East China Sea. From the corresponding surface winds, the episodic northward surface flow bursts appear to be associated with abrupt changes from the strong northerly win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…The basin-scale synoptic variation of YSWC is associated with a counterclockwise rotary wave response to the strong northerly wind bursts. The rotary wave had been indicated in the results of Hsueh et al (1986) and Hu et al (2017). Strong northerly wind burst pushes water in the Bohai Sea move southward and forms a northward SSH drop.…”
Section: Discussionmentioning
confidence: 90%
“…The basin-scale synoptic variation of YSWC is associated with a counterclockwise rotary wave response to the strong northerly wind bursts. The rotary wave had been indicated in the results of Hsueh et al (1986) and Hu et al (2017). Strong northerly wind burst pushes water in the Bohai Sea move southward and forms a northward SSH drop.…”
Section: Discussionmentioning
confidence: 90%
“…The spring‐neap tidal variation is normally a factor that affects the current intensity, but this variation is too weak in the Bohai Sea to change the seasonal water circulation (Wang et al, ), let alone the entirely different winter pattern in this study (Figure a). The local winds are therefore assumed to be a major force in driving currents and waves, setting up ΔMSL and even changing the regional circulation, especially in winter (Hu et al, ; Wang et al, ; Zhang et al, ; Zhao & Shi, ). Furthermore, the episodic wind reversal before and during the winter PAM cruise was likely the major reason for the atypical water intruding into the Bohai Sea (Figure a).…”
Section: Discussionmentioning
confidence: 99%
“…This monthly or seasonal pattern has been verified by moorings and models and widely used in estimating the long‐term sediment transport through the Bohai Strait (e.g., Bi et al, ; Bian et al, ). However, recent studies illustrates that the path and strength of the YSWC are sensitive to the synoptic events, such as typhoons, winter storms, and episodic wind relaxations (Ding et al, ; Hu et al, ; Wu et al, ). As the major flow into the Bohai Sea, whether such changes in the YSWC affect the sediment exchange through the Bohai Strait remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In winter, the Yellow Sea Warm Current (YSWC) has been widely studied because of its prominent hydrographic and upwind features (Hsueh, ; Huang et al, ; Lin & Yang, ; Tak et al, ). The YSWC significantly influences frontal circulation and the heat and water exchange in the Yellow Sea (Lie et al, , ; Pang et al, ), and its synoptic variation has been studied with numerical models in recent years (Ding et al, ; Hu et al, ; Li et al, ). These studies showed that after a strong northerly wind burst, a strong northward YSWC forms in the Yellow Sea trough and is associated with large‐scale SSH variations.…”
Section: Discussionmentioning
confidence: 99%